2022
DOI: 10.1038/s41598-022-26489-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel sulfonated poly (vinyl alcohol)/carboxy methyl cellulose/acrylamide-based hybrid polyelectrolyte membranes

Abstract: Novel polyelectrolytic hybrid membranes are prepared by blending carboxy methyl cellulose (CMC)-polyvinyl alcohol (PVA)-acrylamide (AA). Succinic acid and chlorosulfonic acid (CSA) are employed as crosslinkers and modifiers, respectively. Additionally, carboxylated carbon nanotube (CCNT) and sulfonated activated carbon (SAC) as fillers are used to attain appropriate chemical and mechanical stability for use as polyelectrolyte membranes (PEM). CMC, PVA, and AA are mixed and treated with CSA, CCNT, and SAC in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Furthermore, the gel fraction analysis was performed to find out the un-cross-linked membrane components and provides an estimation of the cross-linking density of the membranes. The results showed that about 76 ± 3% of gel fraction percentage was obtained for SPVA/MoS 2 -0.3% membranes due to increased cross-linking density from sulfonation . Sulfonation introduced more -SO 3 H groups attached to the polymer chains in the membrane.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Furthermore, the gel fraction analysis was performed to find out the un-cross-linked membrane components and provides an estimation of the cross-linking density of the membranes. The results showed that about 76 ± 3% of gel fraction percentage was obtained for SPVA/MoS 2 -0.3% membranes due to increased cross-linking density from sulfonation . Sulfonation introduced more -SO 3 H groups attached to the polymer chains in the membrane.…”
Section: Resultsmentioning
confidence: 98%
“…It is known that the transport of protons across the membrane depends on a vehicular (migration of hydrated protons, H 3 O + ) or Grotthuss (proton hopping) mechanism using bound water present in the membrane. Protons in the form of hydronium ions (H 3 O + ) get transported throughout the membranes via the water molecules present in them. , PVA-based membranes have high water uptake due to the hydrophilic nature of PVA. However, the cross-linked PVA shows lower water uptake with increasing cross-linking density. , The water uptake behavior of pristine and composite membranes for a 24 h study has been shown in Figure d.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations